AB0571 Birmingham vasculitis activity score more than 9.5 at diagnosis is an independent predictor of refractory disease of granulomatosis with polyangitis. (15th June 2017) - You, J; Kim, HJ; Lee, S-W
Abstract : Background: Granulomatosis with polyangiitis (GPA), that is identical to what has been called Wegener's granulomatosis, is one of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV). GPA is characterized by necrotising granulomatous inflammation usually affecting small to medium vessels, and it often involves the upper and lower respiratory tracts and commonly provokes necrotising glomerulonephritis. It has been reported that the mortality rate in untreated patients increased up to 90% within 2 years after diagnosis, and the overall mortality rates were ranging from 12% to 44% within 4 to 10 years. The major causes of death are known as cardiovascular disease, adverse events of immunosuppressive agents and major organ involvement of GPA. If there might be predictors of relapse or refractory disease of GPA during the follow-up duration, they can help physicians to select the induction therapeutic regimens, decide the duration of the maintenance therapeutic regimens and adjust the follow-up interval in order to improve the disease course of GPA. Objectives: We investigated whether clinical manifestations, anti-neutrophil cytoplasmic antibodies (ANCAs), Birmingham vasculitis activity score (BVAS) for granulomatosis with polyangiitis (GPA) and five factor score (FFS) at diagnosis can predict relapse or refractory disease in 30 histology-proven GPA patients with the follow-up duration ≥12 weeks. Methods: We reviewed the medical records of 30 GPA patients. We collected clinical data, ANCAs, BVAS for GPA, FFSs at diagnosis, and we compared variables between the two groups based on relapse or refractory disease. The optimal cut-offs were extrapolated. Multivariate logistic regression and Cox hazard model analyses were conducted to identify predictors of refractory disease. Results: The mean age and follow-up duration of patients were 63.3 years old and 45.2 months. The mean initial BVAS for GPA, FFS (1996) and FFS (2009) were 5.4, 0.6 and 1.0. There were no significant predictors of relapse. The mean BVAS for GPA, FFS (1996) and FFS (2009) of patients with refractory disease were higher than those without (p<0.05 for all). Patients having BVAS for GPA ≥9.5, FFS (1996) ≥2 and FFS (2009) ≥2 exhibited significantly enhanced risk of refractory disease than those having not (RR 23.0, RR 11.0, and RR 55.0, respectively), and low cumulative refractory disease free survival rates. Multivariate Cox hazard model analysis proved BVAS for GPA ≥9.5 was an independent predictor of refractory disease during the follow-up duration (OR 12.892). Conclusions: BVAS for GPA ≥9.5 was an independent predictor of refractory disease during the follow-up duration ≥12 weeks. References: Jennette JC, Falk RJ, Bacon PA, et al. (2013) 2012 revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides. Arthritis Rheum 65(1), 1–11. Acknowledgements: This study was supported by a faculty research grant of Yonsei University College of Medicine (6–2016–0145) and by a grant from the Korea Health Technology R&D Project through the Korea Health Industry Development Institute, funded by the Ministry of Health and Welfare, Republic of Korea (HI14C1324). Disclosure of Interest: None declared